The little book of prayers - Schiller, David ([Place of publication not identifed] : [publisher not identified], 1996)
Here, gathered from poets and theologians, oral traditions and spirituals, private letters and holy books, is a collection of prayers from around the world and across time.
Keywords: PRAYER -- COLLECTIONS